High framerate photoacoustic imaging of blood clots - Sivasubramanian, Kathyayini (2019)
Deep vein thrombosis (DVT) is a disorder that occurs when a blood clot (thrombus) forms in one or more of the deep veins in your body, usually in your legs. Deep vein thrombosis can cause leg pain or swelling, but also can occur with no symptoms. If the clot moves to the vital organs like lungs, heart, brain etc., it can be very fatal and can cause death to the individual. Diagnosing it at early stages is very crucial to decide the treatment strategy. The most commonly used techniques that are used for the diagnosis includes ultrasound, x-ray, CT, etc. For definitive diagnosis contrast agents are required for better visualization of the blood clots and harmful radiations are used. For label free imaging of the blood clots, photoacoustic imaging can be used. To perform in-vivo photoacoustic imaging, high framerate imaging is needed as the velocity of the blood in the veins is between 3 cm/s to 14 cm/s. In this work, we have shown high framerate photoacoustic imaging at different framerates of 5, 10, 50, 100, 500, 1000, 2000 and 3000 fps using a pulsed laser diode of 7000 Hz frequency. We have demonstrated label free imaging of blood clots at 803 nm. Blood clot has at least 1.5 times higher SNR compared to blood and can be clearly visualized against blood as background. High framerate photoacoustic imaging can be used for label free diagnosis of deep vein thrombosis.